Analysis of Income on the Partnership Program-based Broiler Business in Regency of North Minahasa, North Sulawesi, Indonesia - L S Kalangi; S O B Lombogia; M N Regar (AIBPM Publisher, 2021)
The partnership program-based broiler farming business (main-plasma), located in Regency of North, Province of North Sulawesi, Indonesia is performed due to the limit of capital, skill, market access and lack of ability in projecting fluctuated market demand. In addition, Covid-19 pandemic has provenly affected broiler farming business, showed by declining broiler’s demand and production, particularly on the decreasing income of farmers. Hence, the objective of this research is to examine if it is there is a difference among total of DOC (Day-Old Chick) input, feed conversion ratio (FCR), mortality rate, weight of harvest, raising period, and harvest time, pre- and during Covid-19 pandemic, and analyze some impacts of the existing Covid-19 pandemic and some different variables on the income of the partnership program-based broiler farming business. Technically, the purposive sampling was employed as the sampling method in selecting districts, villages, and farmers. Then, data was analyzed by the paired t-test sample using SPSS 22 and multiple-regression analysis by E-views 11 program. As the result, the paired t-test sample shows that variable of income, total of DOC (Day-Old Chick), FCR, mortality rate, rate of broiler’s weight, raising period, and harvest time in pre- and during Covid-19 pandemic was significantly different, where the value of Sig. (2-tailed) was < 0.05, while, the variable of total of DOC and raising period had significantly positive impact on income, variable of FCR and harvest time had significantly negative impact on farmer’s income. Variable of dummy pandemic could decrease farmer’s income in the partnership program-based broiler farming business; however, it was unimportant.